2020
DOI: 10.1111/1346-8138.15366
|View full text |Cite
|
Sign up to set email alerts
|

Cost of illness study for adult atopic dermatitis in Japan: A cross‐sectional Web‐based survey

Abstract: Atopic dermatitis is a pruritic, eczematous dermatitis, the symptoms of which chronically fluctuate with remissions and relapses. Although a high psychosomatic and economic burden caused by atopic dermatitis is expected, few studies have been conducted estimating the cost of illness, including the self‐medication costs and productivity loss due to atopic dermatitis. The aim of this study was to conduct a cross‐sectional, Web‐based survey of the direct medical costs, self‐medication costs and productivity loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 18 publications
8
38
0
Order By: Relevance
“…Furthermore, the results across the EU5 for both direct and indirect costs are similar to those reported in The Netherlands [8]. The results of this study are also similar to a cross-sectional study in Japan, which found that cost per adult patient with AD increased with disease severity [24]. These findings reaffirm the impact that AD, particularly moderate-to-severe AD, can have on the healthcare system and overall society.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, the results across the EU5 for both direct and indirect costs are similar to those reported in The Netherlands [8]. The results of this study are also similar to a cross-sectional study in Japan, which found that cost per adult patient with AD increased with disease severity [24]. These findings reaffirm the impact that AD, particularly moderate-to-severe AD, can have on the healthcare system and overall society.…”
Section: Discussionsupporting
confidence: 86%
“…23 Murota et al . 24 recently conducted a WPAI survey on 400 patients with atopic dermatitis in Japan, and noted absenteeism of 2.1–5.5% and presenteeism of 31.4–31.8%, demonstrating similarly declined work performance to that observed in our survey. Furthermore, the annual societal loss associated with productivity loss was ¥2.5 trillion (approximately ¥208.3 billion/month).…”
Section: Discussionsupporting
confidence: 72%
“…Hamm et al22 examined disease characteristics and func-8% reduction in productivity, with more severe disabilities due to urticaria (33.8%), atopic dermatitis (38.7%), eczema/dermatitis (41.0%), and psoriasis (26.7%) 23. Murota et al24 recently conducted a WPAI survey on 400 patients with atopic dermatitis in Japan, and noted absenteeism of 2.1-5.5% and presenteeism of 31.4-31.8%, demonstrating similarly declined work performance to that observed in our survey. Furthermore, the annual societal loss associated with productivity loss was ¥2.5 trillion (approximately ¥208.3 billion/month).…”
supporting
confidence: 75%
“…We showed that Japanese patients with AD have impaired HRQoL, work productivity, and activity, which supports the findings of previous studies. [16][17][18][19] For example, Arima et al 16 reported that in Japanese patients with AD absenteeism, presenteeism, overall work impairment, and activity impairment were 4.0 ± 12.3%, 28.6 ± 25.3%, 30.6 ± 27.2%, and 32.2 ± 27.9%, respectively. In our study, the respective values were 6.3 ± 19.1%, 27.4 ± 27.8%, 30.4 ± 30.7%, and 31.4 ± 28.8%, indicating that the participants in our study represented typical Japanese patients with AD.…”
Section: Discussionmentioning
confidence: 99%